Armour Fringe - Unknown
Detail of the fur mosaic on Tlingit armour. The bottom of a formline bird figure can also be seen on the garment. Not typically Tlingit fur mosaic. Likely traded from Siberia. Similar motifs are found on bowls and in basketry.